Directional Bias in Molecular Photogearing Evidenced by LED-Coupled Chiral Cryo-HPLC - Gnannt, Frederik; Gerwien, Aaron; Waldmannstetter, Sven; Gracheva, Sofia; Dube, Henry (Angewandte Chemie International Edition, 2024)
Molecular gearing systems are technomimetic nanoscale analogues to complex geared machinery in the macroscopic world. They are defined as systems incorporating intermeshed movable parts which perform correlated rotational motions by mechanical engagement. Only recently, new methods to actively drive molecular gearing motions instead of relying on passive thermal activation have been developed. Further progress in this endeavor will pave the way for unidirectional molecular gearing devices with a distinct type of molecular machine awaiting its realization. Within this work an essential step towards this goal is achieved by evidencing directional biases for the light-induced rotations in our molecular photogear system. Using a custom-designed LED-coupled chiral cryo-HPLC setup for the in situ irradiation of enantiomeric analytes, an intrinsic selectivity for clockwise or counterclockwise rotations was elucidated experimentally. Significant directional biases in the photogearing processes and light-induced single bond rotations (SBRs) are observed for our photogear with directional preferences of up to 4.8 : 1. Harnessing these effects will allow to rationally design and construct a fully directional molecular gearing motor in the future.
CRIS-Team Scopus Importer:2024-08-30
Keywords: analytical methods; molecular gears; molecular machines; photochemistry